1990
DOI: 10.1111/j.1399-6576.1990.tb03033.x
|View full text |Cite
|
Sign up to set email alerts
|

Does ephedrine influence newborn neurobehavioural responses and spectral EEG when used to prevent maternal hypotension during caesarean section?

Abstract: The recovery of 16 infants born by elective caesarean section with spinal anaesthesia, in which either ephedrine or fluid load was used to prevent maternal hypotension, were studied using Scanlon's neurobehavioural tests and a computerized EEG. Neurobehavioural testing showed no differences between the ephedrine and the non-ephedrine groups of infants at ages of 3 h, 1 day, 2 days and 4-5 days, whereas the spectral EEG showed significant differences between the two groups during the first 2 h after delivery, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In restricting the metaanalysis to only trials that had adequate allocation concealment 1,4,5,26 the overall RR was 0.69 (95% CI, 0.58 to 0.83) with no evidence of heterogeneity (Q statistic = 2.04, df = 3, P = 0.56). In trials where allocation concealment was unclear, 6,7,11,21,24,25,27 the overall RR was 0.76 (95% CI, 0.59 to 0.99) with no evidence of heterogeneity (Q statistic = 11.50; df = 7; P = 0.12).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In restricting the metaanalysis to only trials that had adequate allocation concealment 1,4,5,26 the overall RR was 0.69 (95% CI, 0.58 to 0.83) with no evidence of heterogeneity (Q statistic = 2.04, df = 3, P = 0.56). In trials where allocation concealment was unclear, 6,7,11,21,24,25,27 the overall RR was 0.76 (95% CI, 0.59 to 0.99) with no evidence of heterogeneity (Q statistic = 11.50; df = 7; P = 0.12).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis performed after excluding Gutsche's trial 7 because of uncertainty about randomization showed that the overall summary effect size was robust (RR, 0.74; 95% CI, 0.65 to 0.85). Another sensitivity analysis performed after exclusion of the trial by Kangas-Saarela et al 27 in which ephedrine was not given unless there was any decrease in arterial pressure to less than the baseline, showed that the overall RR was 0.73 (95% CI, 0.61 to 0.86). Kangas-Saarela et al 27 showed that there was no difference between giving ephedrine or fluid intervention for the prevention of hypotension (RR,1.00; 95% CI, 0.37 to 2.73).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations